2017
DOI: 10.1111/jre.12458
|View full text |Cite
|
Sign up to set email alerts
|

Increasing popularity of waterpipe tobacco smoking and electronic cigarette use: Implications for oral healthcare

Abstract: Cigarette smoking increases the risk of developing several systemic conditions including cancer, cardiovascular and pulmonary diseases. Cigarette smoking is also detrimental to oral health as it increases the incidence and severity of oral cancer, periodontal diseases, and periimplantitis, as well as impacting negatively dental patients’ response to therapy. Therefore, consideration of smoking behavior and recommendation of smoking cessation are important parts of dental treatment planning. However, cigarettes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 129 publications
(158 reference statements)
3
64
0
7
Order By: Relevance
“…However, there exists compelling evidence about the harms of waterpipe smoking and detrimental effect on long-term health outcomes [7,8]. More specifically, several systematic reviews and metaanalyses have demonstrated the association between WTS and increased risk of lung cancer, cardiovascular diseases, abnormal pulmonary function, low birth weight, and periodontal diseases [4,[9][10][11]. Despite the evidence, the incorrect public perception of reduced harm is possibly driven by the introduction of flavored waterpipe tobacco (also known as Maassel), the advancement of global communication particularly the internet, and the lack of enforcement of waterpipe tobacco control policies [6,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, there exists compelling evidence about the harms of waterpipe smoking and detrimental effect on long-term health outcomes [7,8]. More specifically, several systematic reviews and metaanalyses have demonstrated the association between WTS and increased risk of lung cancer, cardiovascular diseases, abnormal pulmonary function, low birth weight, and periodontal diseases [4,[9][10][11]. Despite the evidence, the incorrect public perception of reduced harm is possibly driven by the introduction of flavored waterpipe tobacco (also known as Maassel), the advancement of global communication particularly the internet, and the lack of enforcement of waterpipe tobacco control policies [6,12].…”
Section: Introductionmentioning
confidence: 99%
“…25 Added to this, studies have reported an increase of electronic cigarette and water pipe smoking and long term research is required on the effects of these innovative habits on the oral cavity. 26 There is a growing body of evidence from studies that genetic factors predispose individuals to periodontal disease. This is seen especially in the rare and more severe forms of periodontitis like early onset periodontitis, now classified as aggressive periodontitis, 27 where family studies have provided good evidence for a prominent genetic role.…”
Section: Risk Factors Associated With Periodontitismentioning
confidence: 99%
“…Abundant evidence has shown that pre-malignant and malignant oral lesions (such as leukoplakia and oral squamous cell carcinoma, respectively) are more often manifested in cigarette smokers compared with non-smokers (Llewellyn et al, 2004, Nayak et al, 2012, Chher et al, 2016, Ramoa et al, 2017). Similar effects of oxidative stress and inflammation are seen in plasma and lungs of smokers and patients with chronic obstructive pulmonary disease (COPD) (Rahman et al, 1996, Rahman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…There is a dearth of studies that have assessed the influence of WS on oral mucosal and periodontal tissues (Ramoa et al, 2017). It is often perceived that WS is less hazardous to health compared with cigarette smoking as the tobacco smoke in the former gets filtered through water, which absorbs a considerable amount of nicotine (Jacob et al, 2013, Jukema et al, 2014, Maziak et al, 2015b); however, results by Javed et al (2016a) showed that WS is as hazardous to periodontal health as traditional cigarette-smoking.…”
Section: Introductionmentioning
confidence: 99%